2019
DOI: 10.1039/c8ra08395a
|View full text |Cite
|
Sign up to set email alerts
|

Microfiltration of raw soy sauce: membrane fouling mechanisms and characterization of physicochemical, aroma and shelf-life properties

Abstract: Membrane fouling mechanisms and characterization of physicochemical, aroma and shelf-life properties of soy sauce subjected to refinement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 40 publications
0
7
2
Order By: Relevance
“…Bechervaise et al [8] obtained C s between 78.9% and 88.3% during removal of thermophilic spores, from gum Arabic streams, by a ceramic membrane with a pore size equal to 0.80 µm. Moreover, turbidity of the permeate obtained in the present work was slightly lower than those reported in previous studies [13,14,25] where purification of various solutions by microfiltration membranes has been studied. For example, in [13] it has been demonstrated that during the clarification of raw soy sauce (feed turbidity: 48 NTU) by a ceramic membrane with the pore size diameter of 0.20 µm allowed to obtain the turbidity of the final product equal to 0.41 NTU and the removal ratio 99.1%.…”
Section: The Efficiency Of Microfiltration Processcontrasting
confidence: 71%
See 3 more Smart Citations
“…Bechervaise et al [8] obtained C s between 78.9% and 88.3% during removal of thermophilic spores, from gum Arabic streams, by a ceramic membrane with a pore size equal to 0.80 µm. Moreover, turbidity of the permeate obtained in the present work was slightly lower than those reported in previous studies [13,14,25] where purification of various solutions by microfiltration membranes has been studied. For example, in [13] it has been demonstrated that during the clarification of raw soy sauce (feed turbidity: 48 NTU) by a ceramic membrane with the pore size diameter of 0.20 µm allowed to obtain the turbidity of the final product equal to 0.41 NTU and the removal ratio 99.1%.…”
Section: The Efficiency Of Microfiltration Processcontrasting
confidence: 71%
“…Moreover, turbidity of the permeate obtained in the present work was slightly lower than those reported in previous studies [13,14,25] where purification of various solutions by microfiltration membranes has been studied. For example, in [13] it has been demonstrated that during the clarification of raw soy sauce (feed turbidity: 48 NTU) by a ceramic membrane with the pore size diameter of 0.20 µm allowed to obtain the turbidity of the final product equal to 0.41 NTU and the removal ratio 99.1%. In turn, Yang et al [25] reported turbidity of permeate equal to 0.81; 0.52 and 0.56 NTU, respectively, during purification of cellulase fermentation broth (feed turbidity: 646 NTU) via ceramic MF membranes with three different pore sizes: 0.05; 0.20, and 0.50 µm.…”
Section: The Efficiency Of Microfiltration Processcontrasting
confidence: 71%
See 2 more Smart Citations
“…Resistance-in-series model is the classical model and it was already applied in our previous work. 22 The permeate ux through the membrane can be calculated in accordance with Darcy's law (eqn (1)):…”
Section: Models Of Membrane Fouling Analysismentioning
confidence: 99%